2022
DOI: 10.1038/s41537-022-00294-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural phenotypes of intrinsic motivation in schizophrenia determined by cluster analysis of objectively quantified real-world performance

Abstract: Intrinsic motivation deficits are a prominent feature of schizophrenia that substantially impacts functional outcome. This study used cluster analysis of innate real-world behaviours captured during two open-field tasks to dimensionally examine heterogeneity in intrinsic motivation in schizophrenia patients (SZ) and healthy controls (HC). Wireless motion capture quantified participants’ behaviours aligning with distinct aspects of intrinsic motivation: exploratory behaviour and effortful activity in the absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…This result is also consistent with the meta-analytic finding that more recently-developed negative symptom scales like the CAINS, which incorporate more experiential elements, reveal more robust relationships to IM than older scales that focus more on directly-observable behaviors [ 24 ]. However, individuals with psychosis may lack insight into impairments in their motivation [ 89 , 90 ], and direct observation and objective behavioral measures provide an important complement to self-reports [ 38 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is also consistent with the meta-analytic finding that more recently-developed negative symptom scales like the CAINS, which incorporate more experiential elements, reveal more robust relationships to IM than older scales that focus more on directly-observable behaviors [ 24 ]. However, individuals with psychosis may lack insight into impairments in their motivation [ 89 , 90 ], and direct observation and objective behavioral measures provide an important complement to self-reports [ 38 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some effort task studies have not found abnormalities [ 28 , 29 ], and studies examining token economies and the impact of monetary incentives on cognitive test performance have shown beneficial effects in schizophrenia consistent with significant EM [ 30 34 ]. IM is harder to operationalize in laboratory studies than EM [ 35 ]; however, fMRI studies of putative neural correlates of IM point to reductions in schizophrenia and psychosis risk [ 16 , 36 , 37 ], as does a recent free-choice behavioral study in schizophrenia [ 38 ].…”
Section: Introductionmentioning
confidence: 99%